Letter from Matthew S. Quay to Margaret M. Booth - Quay, Matthew Stanley (1894)
Matthew S. Quay (1833-1904) of the United States Senate writes to inform Margaret M. Booth née Cardeza that the bill for her relief is now pending and Acting Chairman of the Senate Committee on Finance, Senator Harris, will expedite its consideration.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Quay, Matthew Stanley, 1833-1904; Martinez Cardeza, Margaret; Mint of the United States; United States Mint